2006
DOI: 10.1111/j.1439-0396.2005.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of commercial dry dog foods by near infrared reflectance spectroscopy

Abstract: Near infrared reflectance spectroscopy (NIRS) was used to predict the nutritional value of dog foods sold in Chile. Fifty-nine dry foods for adult and growing dogs were collected, ground and scanned across the visible/NIR range and subsequently analysed for dry matter (DM), crude protein (CP), crude fibre (CF), total fat, linoleic acid, gross energy (GE), estimated metabolizable energy (ME) and several amino acids and minerals. Calibration equations were developed by modified partial least squares regression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 8 publications
9
23
2
1
Order By: Relevance
“…9 In another work, the mineral composition of dog feeds commercialized in Brazil and determined by neutron activation analysis, showed that Fe and K concentrations were in accordance with AAFCO, while the concentrations of Ca and Zn were below and above the set levels, respectively. 3 In contrast, reflectance infrared spectrometry was used to study dog feeds marketed in Chile, and it was reported mean values for Ca, K, Mg and P of 16.7, 10.5, 6.1 and 1.8 g kg -1 , respectively, which were in accordance with AAFCO, except for Mg. 1 Other minerals were also determined, including Fe (353.8 mg kg -1 ), Cu (29.5 mg kg -1 ), Mn (66.6 mg kg -1 ) and Zn (180.2 mg kg -1 ), that were in agreement with the AAFCO and the values found in this study. 1 In a study carried out in the United Kingdom (UK), the concentrations found for macroelements Ca, P, S, Mg and K were higher than those found in this work, with maximum of 18 and 32% for cat and dog feeds, respectively.…”
Section: Determination Of Mineral Content and Humidity In Feeds For Dsupporting
confidence: 88%
See 2 more Smart Citations
“…9 In another work, the mineral composition of dog feeds commercialized in Brazil and determined by neutron activation analysis, showed that Fe and K concentrations were in accordance with AAFCO, while the concentrations of Ca and Zn were below and above the set levels, respectively. 3 In contrast, reflectance infrared spectrometry was used to study dog feeds marketed in Chile, and it was reported mean values for Ca, K, Mg and P of 16.7, 10.5, 6.1 and 1.8 g kg -1 , respectively, which were in accordance with AAFCO, except for Mg. 1 Other minerals were also determined, including Fe (353.8 mg kg -1 ), Cu (29.5 mg kg -1 ), Mn (66.6 mg kg -1 ) and Zn (180.2 mg kg -1 ), that were in agreement with the AAFCO and the values found in this study. 1 In a study carried out in the United Kingdom (UK), the concentrations found for macroelements Ca, P, S, Mg and K were higher than those found in this work, with maximum of 18 and 32% for cat and dog feeds, respectively.…”
Section: Determination Of Mineral Content and Humidity In Feeds For Dsupporting
confidence: 88%
“…The global feed industry for dogs and cats has grown extensively, particularly in Brazil, which occupies the second place in cat and dog feed production behind the United States. [1][2][3] Various types of feed are available in the market, and they can be differentiated according to the ingredients, size and breed of the animal, and for animals predisposed to a specific disease. [2][3][4] Dry feeds should present a final humidity between 10 and 12% 5 and be formulated to achieve a specific amount of nutrients, using as raw material cereal grains and products derived from animal sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions employed for the direct spectrometric determination of mineral elements in foods vary from visible (Alomar et Cozzolino et al, 2008;Font et al, 2004aFont et al, , 2005Lucas et al, 2008) to near infrared (NIR) (Alomar et al, 2006;Andueza et al, 2004;Collell et al, 2010;Cozzolino and Moron, 2004;Cozzolino et al, 2008Cozzolino et al, , 2011Font et al, 2004aFont et al, , 2004bFont et al, , 2005Gonzalez-Martin et al, 2002, 2007Huang et al, 2008;Lebot et al, 2009;Lucas et al, 2008;Masoum et al, 2011;Moron and Cozzolino, 2002;Moros et al, 2008;Plans et al, 2012;Reeves, 2001;Reeves and Van Kessel, 2002;Sauvage et al, 2002;Wu et al, 2009) and mid infrared (MIR) (Moros et al, 2006;Reeves, 2001;Reeves and Van Kessel, 2002;Soyeurt et al, 2009;Wu et al, 2009); measurement signals were obtained by absorbance and reflectance, also including contact and remote procedures based on the use of fiber optics (Collell et al, 2010;Gonzalez-Martin et al, 2002, 2007.…”
Section: Infrared Measurementsmentioning
confidence: 99%
“…Furthermore, Near Infra Red Spectroscopy (NIRS) has become one of the most powerful tools for the rapid, non-destructive estimation of the chemical composition and the nutritive evaluation of feeds and mixed diets. However, few studies have been carried out on pet food to assess NIRS potential to predict its chemical composition, apparent digestibility, digestible nutrients and energy content (Castrillo et al, 2005;Alomar et al, 2006), probably because of the difficulty of obtaining enough samples with in vivo data for robust calibration.…”
Section: Introductionmentioning
confidence: 99%